Tolerância ao calor de borregos criados em Mato Grosso : parâmetros produtivos, fisiológicos e comportamentais - Costa, Fabiana Gomes da (2017)
The experiment was conducted in order to evaluate the heat tolerance of lambs raised in Mato Grosso on productive parameters (nutrient intake, apparent digestibility and performance), behavioral activity (grazing, ruminating, idleness, water intake) and physiological parameters Respiratory rate(RR), heart rate (HR), rectal temperature (RT), pelt temperature (PT) and sweating rate (SR)).The study was carried out during the drywater transition period, with a duration of 60 days, two experimental periods of 30 days each. Twenty lambs, newly weaned, uncastrated, mestizos (Santa Inês x Dorper), with a mean initial weight of 22.8 kg were used, five animals per treatment, which were kept under grazing on four pickets composed of Brachiariadecumbens. The animals were randomly distributed in a completely randomized design in a factorial scheme (2x2) in the following treatments: T1: Picket with direct solar radiation and 15% CP in the supplement; T2: Sombre picket and 15% CP in the supplement; T3: Picket with direct solar radiation and 25% CP in the supplement; T4: Sombre picket and 25% CP in the supplement. The studied variables were submitted to analysis of variance using the statistical software R, and the means were compared using tukey test considering 5% of significance. There was no effect (P> 0.05) of the interaction between the factors for dry matter intake, neutral detergent fiber intake, neutral detergent fiber corrected for ash and protein, non-fibrous carbohydrate intake, total carbohydrate intake, Total digestible nutrients intake, expressed as g day-1 and% of body weight (BW), and metabolizable energy expressed as DM / kg DM, but an effect (P <0.05) was observed for CP intake in g day-1 and %BW since the animals that were in full sun supplemented with 15% CP, obtained lower CP intake than the other treatments.There was no effect (P> 0.05) of the interaction between the factors for crude protein digestibility coefficient (CPDC), neutral detergent fiber (NDFDC), neutral detergent fiber corrected for ash and protein (NDFDCap), non-fibrous carbohydrate (NFCDC), total carbohydrates (TCDC), and total weight gain and mean daily gain. However, the use of sombrite influenced the dry matter digestibility coefficient (DMDC). The inclusion of different CP levels in the supplement did not influence (P> 0.05) the DMDC, TCDC, but had an effect (P <0.05)on CPDC, NDFDC, NDFDCcp and NFCDC, with CPDC, NDFDC and NDFDCap were higher for treatments with 25% PB in the supplement.There was no effect (P> 0.05) of the interaction between grazing, ruminating and idleness activities. However, a significant effect (P <0.05) on the frequency of water intake was observed in the treatments in which the animals were exposed to direct solar radiation during the grazing period, regardless of the CP level in the supplement. There was no effect (P> 0.05) of the interaction between the factors on the RR, HR, PT, but there was an effect (P <0.05) of the interaction for the RT and SR. The use of sombre did not influence (P> 0.05) the RR, HR, RT, however it influenced the PT and SR. RR, PT and SR were influenced (P <0.05) by inclusion of crude protein levels in the supplement, but there was no effect (P> 0.05) for HR and RT. The use of artificial shading supplemented with 25% of crude protein provided better productive, behavioral and physiological responses of lambs during the dry-season transition period, since animal production in tropical regions may be limited mainly by caloric stress.